Towards a Medically Approved Technology for Large-Scale Stem Cell Banks: Tools and Method - Katsen-Globa, A.; Schulz, J.C.; Baunach, J.S.; Ehrhart, F.; Oh, Y.-J.; Schön, U.; Kofanova, O.; Beier, A.F.J.; Wiedemeier, S.; Metze, J.; Shirley, S.; Spitkovsky, D.; et al. (Проблемы криобиологии и криомедицины, 2008)
The importance, of the development of stem cell cryobanking has increased recently with an augmentation of stem cell research and its therapeutic applications. The development of therapies is, among other things, limited by high sensitivity of stem cells to freezingthawing procedures. Thus, new approaches are needed for preservation and related evaluation methods, as well as new technologies for long term storage of large numbers of stem cells. Here we present selected recent improvements of stem cell cryopreservation, e.g. for freezing of adherent human embryonic stem cells using gel-like matrices. We report the application and performance of novel microsystem-based cryosubstrates and devices and describe new evaluation methods and the results of a thermal stress cycle study.